2018
DOI: 10.1063/1.5010826
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the pure monoclinic phase of WO3 and WO3-Ag nanostructures for non-enzymatic glucose sensing application with theoretical insight from electronic structure simulations

Abstract: Here, we report the controlled hydrothermal synthesis and tuning of the pure monoclinic phase of WO3 and WO3-Ag nanostructures. Comparative electrochemical nonenzymatic glucose sensing properties of WO3 and WO3-Ag were investigated by cyclic voltammetry and chronoamperometric tests. We observed enhanced glucose sensing performance of WO3-Ag porous spheres as compared to bare WO3 nanoslabs. The sensitivity of the pure WO3 nanoslabs is 11.1 μA μM−1 cm−2 whereas WO3-Ag porous spheres exhibit sensitivity of 23.3 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 43 publications
5
22
0
Order By: Relevance
“…The CV curve shows the quasi-rectangular nature due to the pseudocapacitive charge storage. The W80 electrode emphasizes the prominent reversible redox reaction, i.e., cathodic and anodic peaks arising from the reduction of W 6+ to W 5+ at the potential of À0.4 V to À0.5 V and À0.35 V to À0.45 V, respectively, which has shown by reaction (b):47 WO…”
mentioning
confidence: 99%
“…The CV curve shows the quasi-rectangular nature due to the pseudocapacitive charge storage. The W80 electrode emphasizes the prominent reversible redox reaction, i.e., cathodic and anodic peaks arising from the reduction of W 6+ to W 5+ at the potential of À0.4 V to À0.5 V and À0.35 V to À0.45 V, respectively, which has shown by reaction (b):47 WO…”
mentioning
confidence: 99%
“…Annealing at 550 °C and above results in WO 3 having monoclinic structure [JCPDS card no. 43-1035 ( ref. 40 )].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this material is widely used in solar photocatalysis [273,296,297], but it has also been demonstrated that this semiconductor material exhibits enhanced chemical sensing properties and is used in several sensing applications [298][299][300][301].…”
Section: Tungsten Trioxidementioning
confidence: 99%